دراسة بعض المؤشرات الحياتية لذبابة الهالوك Phytomyza orobanchia Kalt. تحت ظروف مخبرية - أحمد, محمد; الرهبان, بهاء; حبق, حنان (Latakia University Journal -Biological Sciences Series, 2013)
أجريت دراسة بيولوجية لذبابة الهالوك Phytomyza orobanchia Kalt على الهالوك المتفرع Orobanche ramosa L. الذي يصيب البندورة في المنطقة الساحلية من سوريا، خلال الموسم الزراعي2011-2012، درست فيها بعض المؤشرات الحيوية لهذه الذبابة وهي: فترة ما قبل وضع البيض، وضع البيض، بعد وضع البيض، عدد البيض الكلي الذي تضعه الأنثى، ومدة التطور الكلية، عند درجتي حرارة 25± 1 ºس، 30 ±1 ºس ورطوبة نسبية 70±5%. بينت النتائج أن الأنثى الملقحة تضع بيضها إفرادياً في أزهار الهالوك المتفرع (كبسولات البذور) وأحياناً ضمن الفروع. وكان متوسط عدد البيض الكلي الذي تضعه الأنثى5.41±12.90 ، 7.53±13.50 بيضة، عند درجتي حرارة 25± 1 ºس، 30 ±1 ºس، على التوالي، مع عدم وجود فروق معنوية . بينما كانت فترة ما قبل وضع البيض 0.79±3.60 يوماً عند درجة حرارة 25± 1 ºس، لتنخفض إلى 0.32±1.90 يوماً عند الدرجة 30 ±1 ºس، مع وجود فروق معنوية. وكانت متوسطات قيم المؤشرات الأخرى (فترة وضع البيض، بعد وضع البيض) أعلى عند الدرجة 25 ±1 ºس، بدون وجود فروق معنوية. للحشرة ثلاثة أعمار يرقية، تتطور اليرقة، ضمن الكبسولة وتتعذر داخلها. وكانت مدة تطور العذراء/أنثى أقل مما هي بالنسبة للعذراء /ذكر، لتكون مدة التطور الكلية لذبابة الهالوك P. orobanchia قد استغرقت 18.5± 3.49، 17.75± 2.99 يوماً بالنسبة للذكور. و17.7±2.93، 16.7±2.6 يوماً بالنسبة للإناث. على درجتي حرارة 25 ± 1 ºس، 30 ±1 ºس على التوالي. A biological study of Phytomyza orobanchia Kalt on branched broomrape (Orobanche ramosa L.) which infest tomato crop, in the coastal region of Syria, was conducted during 2011/2012 growing season. It included a study of some biological parameters: The preoviposition, oviposition, post oviposition, total number of eggs laid per female, and total developmental period, at 25 ± 1ºc, 30 ± 1ºc and 70±5% RH. The results showed that the fertilized females insert their eggs singly in the flowers (seed capsules) and sometimes in the shoots of O. ramosa. The average of the total number of eggs per female was 12.90 ± 5.41, 13.50 ± 7.53 at 25 ± 1ºc, 30 ± 1ºc, respectively, without significant differences. The preoviposition period was 3.60 ± 0.79 day at 25 ± 1ºc, and decreased to 1.90 ± 0.32 day at 30 ± 1ºc with significant differences. The average values of other biological parameters (oviposition, post oviposition) were higher at 25 ± 1ºc, without significant differences. This insect has three larval instars, and the larvae complete its development and pupate inside seed capsules. the developmental period of pupa for female was shorter than pupa for male, and the total developmental period of P. orobanchia occupied 18.5 ± 3.49, 17.75 ± 2.99 day for male, and 17.7 ± 2.93, 16.7± 2.6 day for female at 25 ±1ºc, 30±1ºc respectively.